PEMBUATAN TINTA STEMPEL BERBAHAN ALAMI DARI BUAH KEDUDUK DENGAN PENAMBAHAN ETANOL [MAKING STAMP INK FROM NATURAL MATERIALS FROM KEDUDUK FRUIT WITH THE ADDITION OF ETHANOL] - Veronika, Nina; Hakim, Rizki Rahman; Linggom, Umar (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
Keduduk fruit is the fruit of the keduduk plant which has many benefits, one of which is as a natural raw material for making stamp ink. The fruit used is fruit that has bloomed or is ripe. Picked keduduk fruit can be used as a natural dye. In this study, the aim was to determine the best quality of stamp ink with variations in ethanol concentration and fruit. Keduduk fruit extract is obtained from the extraction process, namely by filtering method, then the results will be used as raw material for making stamp ink. Making stamp ink can be done by adding vinegar as a color fixing agent produced from keduduk fruit, salt which is useful as a preservative which can prevent fungal and bacterial attacks, ethanol functions as a drier agent, namely an ingredient that accelerates the ink drying process. The process of making stamp ink in this research uses a variety of raw materials for kejadi fruit, namely 50 grams, by mixing 10 mL of vinegar, varying ethanol concentrations of 96%, 86%, 76%, 66%, 56%, 10 mL and 5 grams of salt. The best quality stamp ink is the 96% ethanol variation which is in accordance with the quality of ink according to SNI 06-1567-1989 which has a density of 1.0489 gr/cm3, a drying time of 30.77 seconds, and is resistant to rubbing, sunlight, water, 96% alcohol, and no clumping.